Mixotrophic ciliate dynamics in two zones of a temperate and highly turbid estuary in South America, Argentina - Rosa E. Pettigrosso; Maximiliano D. García; Román Ruibrig; M. Sofía Dutto; María López Morales; Mónica S. Hoffmeyer (Ecología Austral, 2016)
Mixotrophy is a feeding strategy by which some organisms combine autrotrophic and heterotrophic activities. The seasonal dynamics of the five most common mixotrophic ciliates were studied monthly in surface layers of the inner and middle zone of the Bahía Blanca estuary, a nutrient-rich, shallow and highly turbid environment in Argentina, from January to December 2009. Temperature, salinity, turbidity and chlorophyll a were recorded, as well as the abundance and biomass of Strombidium capitatum, Strombidium acutum, Cyrtostrombidium sp., Lohmanniella oviformis and Tontonia appendiculariformis. The highest mixotrophic ciliate abundance was recorded during the austral winter (June-July) in the inner zone, meanwhile in the middle zone of the estuary the presence of these ciliates was almost null. The highest chlorophyll contribution derived from mixotrophic ciliates to total chlorophyll a ranged from 6% in the inner zone to 23% in the middle zone, both registered in autumn. The low abundance of mixotrophs in the middle zone of the estuary during the winter, as is usually observed in other coastal ecosystems, could be explained through a higher grazing pressure in this zone (top-down control) by mesozooplankton (e.g., copepods) in comparison to the inner zone. The secondary bloom of phytoplankton consistently observed during the last summers dominated by small sized diatoms and nanoplankton phytoflagelates, could have sustained the high abundance of mixotrophic ciliates registered in the middle zone in autumn and summer.